On the boundaries of translatability: dialectal textual variation - Bolaños Cuéllar, Sergio (Íkala, Revista de Lenguaje y Cultura, 2004)
This article presents a brief account of the problem of translatability in texts dialectally marked. A definition of dialect and the assessment of this linguistic phenomenon in translation studies are discussed. A Dynamic Translation Model (DTM) is also introduced as a framework where the problem could be solved by resorting to the notion of dialectal connotation Received: 15-03-04 / Accepted: 13-07-04 How to reference this article: Bolaños Cuéllar, S. (2004). Sobre los límites de la traducibilidad: la variación dialectal textual. Íkala. 9(1), pp. 315 – 347